Customary Legitimacy and the Reproduction of Local Political Elite Power in Bone Regency: A Literature Review - Melda Agriya Ningsih Nurdin; Rabina Yunus; Irwan Ade Saputra (Journal of Contemporary Local Politics, 2025)
This article examines how customary legitimacy contributes to the reproduction of local political elite power in Bone Regency and how it is negotiated within formal state mechanisms. Using a Systematic Literature Review (SLR), the study analyzes 200 peer-reviewed journal articles published between 2015 and 2025, retrieved from Scopus, Google Scholar, DOAJ, and Garuda databases. The selected literature was screened through explicit inclusion and exclusion criteria and analyzed using thematic coding supported by NVivo 12 Pro, complemented by bibliometric mapping with VOSviewer. The findings reveal that customary legitimacy manifested through aristocratic titles, Bugis values such as ade’, siri’, and lempu, and kinship networks functions as symbolic and social capital in local political competition. Local elites actively reproduce these customary symbols through electoral campaigns, ritual participation, and genealogical narratives to strengthen political authority. The review also identifies recurring tensions between customary legitimacy and formal state administrative mechanisms, particularly in the recognition and verification of aristocratic titles; however, these tensions are largely managed through negotiation and institutional adaptation rather than open conflict. This study contributes to the literature by demonstrating the transformation of customary symbols and aristocratic status into political capital within modern democratic institutions, highlighting a hybrid configuration in which traditional authority is strategically integrated into formal state governance in Bone